Switching between ground and excited states by optical feedback in a quantum dot laser diode - Virte, Martin; Breuer, Stefan; Sciamanna, Marc; Panajotov, Krassimir (Applied physics letters, 2014)
We demonstrate switching between ground state and excited state emission in a quantum-dot laser subject to optical feedback. Even though the solitary laser emits only from the excited state, we can trigger the emission of the ground state by optical feedback. We observe recurrent but incomplete switching between the two emission states by variation of the external cavity length in the sub-micrometer scale. We obtain a good qualitative agreement of experimental results with simulation results obtained by a rate equation that accounts for the variations of the feedback phase.